Answer:
Option C. x + 12 ≤ 2(x – 3)
Explanation:
From the question, we obtained the following information:
x + 12 ≤ 5 – y .......(1)
5 – y ≤ 2(x – 3) ....... (2)
To know which option is correct, do the following:
From equation 2,
5 – y ≤ 2(x – 3)
Thus, we can say
5 – y = 2(x – 3)
Now, we shall substitute the value of 5 – y into equation 1 as shown below:
x + 12 ≤ 5 – y
5 – y = 2(x – 3)
x + 12 ≤ 2(x – 3)
From the above illustration, we can see that if x + 12 ≤ 5 – y and 5 – y ≤ 2(x – 3), then x + 12 ≤ 2(x – 3) must be true.
Option C gives the correct answer.